Preliminary surveys of the distribution of Chromolaena odorata in Bangladesh - S.M. Rezaul Karim (2013)
Chromolaena odorata (L.) R.M. King and H. Robinson (Asteraceae), commonly known as Siam weed, is a notorious agricultural and environmental weed, and can cause allergenic effects in humans and health impacts if cattle consume the weed. In preliminary roadside distribution surveys conducted in Bangladesh in 2009, a vast area of land, especially along roadsides, in fallow land and horticultural gardens in the districts of Rajshahi, Jessore, Chittagong, Manikganj, Bandarban, Patuakhali, Faridpur, Mymensingh, Tangail and Dhaka, was infested with C. odorata. Detailed surveys to determine the entire distribution of C. odorata in the country, a risk assessment of the weed for inclusion in the list of noxious weeds, as well as detailed studies for sustainable management of the weed are required.